Application of Geographical Information System and statistical methods for effective marine fisheries law enforcement in the South China Sea - Kasmi, Sutarji; Hashim, Nor Rasidah (Australian Naval Institute, 2009)
The trends of intrusion of foreign fishing vessels into Malaysia's fisheries waters in the South China Sea are analysed, the efforts made by the various Malaysia's maritime enforcement agencies to contain them are studied and new approaches for more effective marine fisheries law enforcement are proposed. Failure on the part of maritime enforcement agencies will cost Malaysia heavily in terms of loss to fisheries.